Penguatan Identitas Nasional Sebagai Upaya Menanamkan Rasa Cinta Tanah Air Pada Generasi Muda - Eli Sabrifha; Tiara Tiara (Jurnal Sains, Teknik, Ekonomi, dan Pendidikan, 2026)
National identity is a crucial element in social, national, and state life. In the era of rapidly developing globalization, Indonesia's young generation faces various challenges that can influence their sense of nationalism and love for their homeland. This paper aims to discuss the importance of strengthening national identity as an educational effort to shape the character of the younger generation, who have a spirit of patriotism and a sense of responsibility for national unity. Using a literature review method, this research examines the elements of national identity, the various challenges that arise, and steps that can be implemented through education, the family environment, and society. The results of the discussion indicate that strengthening national identity requires good cooperation between schools, the government, families, and society so that national values can be optimally instilled.